2022
DOI: 10.20944/preprints202209.0383.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations Between Obstructive Sleep Apnea (OSA) and COVID-19 Infection and Hospitalization Among U.S. Adults <strong> </strong>

Abstract: Background: Medical comorbidities increase the risk of severe COVID-19 infection. In some studies, obstructive sleep apnea (OSA) has been identified as a comorbid condition that is associated with an increased prevalence of COVID-19 infection and hospitalization, but few have investigated this association in a general population. Research Question: In a general population, is OSA associated with increased odds of COVID-19 infection and hospitalization and are these altered with COVID-19 vaccination? Study Desi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
(69 reference statements)
0
4
1
Order By: Relevance
“…27 Previous results from the COPE initiative indicated that receiving a COVID-19 booster vaccination reduced the risk of COVID-19 hospitalization attributable to OSA. 17 In contrast, we did not find that boosted vaccination for COVID-19 affected the odds of developing PASC related to insomnia, poor sleep quality or short sleep duration.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…27 Previous results from the COPE initiative indicated that receiving a COVID-19 booster vaccination reduced the risk of COVID-19 hospitalization attributable to OSA. 17 In contrast, we did not find that boosted vaccination for COVID-19 affected the odds of developing PASC related to insomnia, poor sleep quality or short sleep duration.…”
Section: Discussioncontrasting
confidence: 82%
“…As done in our previous studies, participants were considered to have symptoms of OSA if they had either of the following combination of symptoms: 1) snoring “three or more times a week” and witnessed apnea or sleepiness “once or twice a week”; 2) witnessed apnea and sleepiness “once or twice a week”. 6,17…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations